Syntheses of Rubidium- and Cesium Triiodides in Supercritical Carbon Dioxide - Xhaxhiu, K.; Mele, A.; Memo, A.; Seiti, B.; Kota, T.; Dule, K. (Asian Journal of Chemistry, 2012)
By knowing the physical-chemical properties of supercritical CO2 and its extended use as an attractive continuous phase for different applications, we employed in this study supercritical CO2 as a reaction medium for syntheses between inorganic species. In this course of investigation, aiming to obtain the ternary compounds M2SnI6 (M = Rb, Cs) in supercritical CO2 using a self made lab-scale system at 200 ºC, 220 bar for one week, instead of the desired product, we obtained the triiodides of rubidium (RbI3) and cesium (CsI3). Small amounts of water, introduced as impurity played a determinant role in the syntheses, meanwhile, the presence of tin(IV) iodide and supercritical CO2 were crucial factors for the occurrence of triiodides.